Antiquities - Ozick, Cynthia (Alfred A. Knopf, 2021)
"Lloyd Wilkinson Petrie, one of the seven surviving trustees of the now defunct (for 34 years) Temple Academy for Boys, is preparing a memoir of his days at the school, intertwined with a description of present events. As he navigates, with faltering recall , between the subtle anti-semitism that pervaded the school's ethos and his fascination with his own family history--in particular, his illustrious cousin, the renowned archaeologist Sir Flinders Petrie (check out his Wikipedia entry!), the source of his interest in antiquity--he reconstructs the story of his encounter from his school days with a younger student named Ben-Zion Elefantin, who seems to belong to a lost ancient Jewish sect. From this seed emerges one of Ozick's most wondrous tales, one that displays her delight in Jamesian irony and the mythical flavor of a Kafka parable, woven into her own distinct voice"--